Good humor, bad taste : a sociology of the joke - Kuipers, Giselinde (Mouton textbook., 2015)
This is an updated edition of Good Humor, Bad Taste: A Sociology of the Joke, published in 2006. Using a combination of interview materials, survey data, and historical materials, it explores the relationship between humor and gender, age, social class, and national differences in the Netherlands and the United States. This edition includes new developments and research findings in the field of humor studies.